Embryo development and live birth resulted from artificial oocyte activation after microdissection testicular sperm extraction with ICSI in patients with non-obstructive azoospermia - Zhang, Xi; Li, Li; Zhang, Wenhong; Luo, Yang; Mao, Yuling; Du, Hongzi; Li, Lei (Frontiers in Endocrinology, 2023)
Introduction: The application of microdissection testicular sperm extraction (micro-TESE) to retrieve the sperm of patients with non-obstructive azoospermia (NOA) has greatly increased. Yet there is little research on artificial oocyte activation (AOA) after intracytoplasmic sperm injection (ICSI) treatment performed on patients who successfully obtained motile and immotile sperm using micro-TESE sperm. Therefore, this study sought to obtain more comprehensive evidence-based data and embryo development outcomes for better consultation of NOA patients who opted to undergo micro-TESE combined with ICSI in vitro fertilization (ICSI-IVF) and see whether it is required to perform AOA in different motile spermatozoa after ICSI. Methods: This retrospective study involved 235 NOA patients who underwent micro-TESE to gather enough sperm for ICSI-IVF between January 2018 and December 2020. A total of 331 ICSI cycles were performed in the 235 couples. Embryological, clinical, and ongoing pregnancy outcomes were demonstrated comprehensively between motile sperm and immotile sperm—AOA and non-AOA. Results: Motile sperm with AOA group (G1) showed significantly higher 2PN fertility rate (64.33% vs. 60.22%, p=0.036), and miscarriage rate (17.65% vs. 2.44%, p=0.018) than motile sperm with non-AOA group (G2). No significant differences were observed in available embryo on day 3 rate and live birth rate between G1 and G2. Immotile sperm with AOA group (G3) displayed significantly higher 2PN fertility rate (67.36% vs. 60.22%, p=0.001) than G2, but significantly lower available embryo rate (26.63% vs.40.74%, p=0.000) and good embryo rate (15.44% vs. 6.99%, p=0.000). After ET, G2 showed higher live birth rate than G3, but with no statistical significance. G3 had a significantly higher miscarriage rate (20.00% vs.2.44%, p=0.014) than G2. Discussion: AOA could help patients with no motile sperm to increase the rate of fertilization and obtain pregnancy rates similar to those in patients with motile sperm, but it does not improve embryo quality and ongoing pregnancy outcomes. For NOA patients with motile sperm by micro-TESE, AOA can increase fertilization rate, but it cannot improve embryo quality and pregnancy outcomes. AOA treatment after ICSI should only be used when immotile sperm are injected, and in cases of teratospermia and suspected poor fertilization when motile sperm are injected.